Hyperbola Language Style in The Raditya Dika's Marmut Merah Jambu Novel - Lazfihma Lazfihma; Meli Afrodita (Indonesian Journal of E-learning and Multimedia (IJOEM), 2023)
This study will describe the form of hyperbole contained in the novel Marmut Merah Jambu by Raditya Dika. The second describes the meaning of hyperbole in the novel Marmut Merah Jambu by Raditya Dika. This research is a type of qualitative research. The source of data in this study is the source of written data found in the novel Marmut Merah Jambu by Raditya Dika. While the data collected included intensive reading of the novel Marmut Merah Jambu by Raditya Dika and then analyzed. The data analyzed are in the form of phrases or sentences containing hyperbole in the novel. Data analysis techniques in this study collected and studied written data from the manuscript of the novel Marmut Merah Jambu by Raditya Dika. The results of this study indicate (1) there are 20 hyperbolein the novel Marmut Merah Jambu (2) The meaning of hyperbole in the novel Marmut Merah Jambu by Raditya Dika is obtained by interpreting sentences containing hyperbole. The meaning of hyperbole style obtained 20 pieces. The meaning of hyperbole in the novel Marmut Merah Jambu by Raditya Dika is as an affirmation in the novel and to beautify the style of language used. As an affirmation, that is for the reader to feel and create imagination based on the hyperbole written by Raditya Dika